La costruzione culturale della vita materiale: dono strategico, economie e relazioni informali nei mercati pubblici - Silvia Lelli (EtnoAntropologia)
After a short theoretical introduction that highlights how field research in public street markets provides a contribution to economic-anthropological theories, street markets turn out to be characterized by a dense social interaction, and by complex intersections of multidirectional policies: within them, the effects of economic and administrative macro-policies imposed 'from above' are visible and, at the same time, in reverse, we can detect here aspects of the local social construction that from grass root level influences the exterior, both in forms of organized resistance against disadvantageous imposed policies, and by spontaneously shaping the social interaction pattern and the identity of the urban neighbourhoods where markets are sited. As arenas in which the possibility and the ability 'to negotiate' symbolic as well as economic values is constantly reproduced, the cultural 'immaterial' component of 'material' life is evident in public markets. As contexts in which different economies – capitalist and non-monetary, formal and informal, where the gift is a social and commercial strategy – are simultaneously ongoing, as spaces of interaction between highly heterogeneous socio-economical classes, between solidarity and exploitation, consumerism, reuse and saving, street markets are aggregates of apparently contradictory, but complementary social qualities. Such ‘disorder’ often makes them target of gentrification, transformation or limitations attempts, but the complexity of their polyhedral configuration seems to guarantee their persistence in history, as resistant forms of socioeconomical exchange, and rare contexts of urban social construction.